2018
DOI: 10.1002/cbin.10958
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of trans fatty acids and their possible roles in the lipid rafts in apoptosis regulation

Abstract: A large number of recent studies are focused on evaluating the mechanism of action of trans fatty acids (TFAs) on the progression of apoptosis. A strong positive association has been reported between TFA and coronary heart disease (CHD), obesity and nonalcoholic steatohepatitis and so on. The present study reviewed the biological effects of trans fatty acids (TFA) and their possible roles in lipid rafts in regulating apoptosis. The following aspects of TFA were included: the research about TFA and diseases aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 88 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…There are many health concerns surrounding TFAs, including associations with increased risk of CHD, obesity and insulin resistance [ 64 ]. Vaccenic acid is metabolised to rumenic acid (c9t11 CLA; CLA9) (discussed below), which is beneficial for human health, in the adipose tissue of both animals and humans, whereas elaidic acid has been closely linked to CHD, steatohepatitis and obesity [ 65 ]. The naturally occurring TFAs found in meat may not be harmful [ 66 ] but due to the challenges of isolating TFAs and examining their direct effect on human health, the UK recommendation is no more than 2% of dietary energy intake should come from TFAs [ 67 ]; however, the evidence does not point towards ruminant-derived TFAs (VA) negatively impacting human health, and in particular, health benefits have been reported as a result of VA consumption [ 58 ].…”
Section: Fatty Acidsmentioning
confidence: 99%
“…There are many health concerns surrounding TFAs, including associations with increased risk of CHD, obesity and insulin resistance [ 64 ]. Vaccenic acid is metabolised to rumenic acid (c9t11 CLA; CLA9) (discussed below), which is beneficial for human health, in the adipose tissue of both animals and humans, whereas elaidic acid has been closely linked to CHD, steatohepatitis and obesity [ 65 ]. The naturally occurring TFAs found in meat may not be harmful [ 66 ] but due to the challenges of isolating TFAs and examining their direct effect on human health, the UK recommendation is no more than 2% of dietary energy intake should come from TFAs [ 67 ]; however, the evidence does not point towards ruminant-derived TFAs (VA) negatively impacting human health, and in particular, health benefits have been reported as a result of VA consumption [ 58 ].…”
Section: Fatty Acidsmentioning
confidence: 99%
“…iTFAs raise LDL (low-density lipoprotein) cholesterol levels and lower HDL (high-density lipoprotein) cholesterol levels, consequently, increasing the risk of coronary heart disease [19]. Moreover, it has been found that consumption of iTFAs increases the risk of atherosclerosis and that TFAs induce apoptosis and inflammation [20]. However, some beneficial effects of TFAs have also been discussed, such as the anticancer properties of animal-origin CLA as well as its ability to fight inflammation and reduce the risk of cardiovascular disease [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Unsaturated trans FAs have different biological properties compared to the cis configuration, and their functions differ based on how they were produced. Trans FAs produced by industrial hydrogenation of plant oils are related to higher risks of CVDs compared to other FA classes (Calder, 2015;Del Razo Olvera et al, 2017;Qiu et al, 2018). On the other hand, trans FAs created by biohydrogenation in ruminants (TVA and CLA) are not associated with heart disease (Kalač, 2011).…”
Section: Fatty Acids Phytochemicals and Human Healthmentioning
confidence: 99%